Global Trends of Artificial Intelligence for Diabetic Wound Care: A Bibliometric Analysis - Erna, Riani; Kartasasmita, Arief S; Boesoirie, Shanti F; Wijana, Wijana; Amin, Ramzi (International Journal of Innovative Research and Scientific Studies, 2025)
This study provides a comprehensive bibliometric analysis of the application of artificial intelligence (AI) in diabetic wound care, focusing on trends, key contributors, and research themes. Using data collected from the Scopus database, the research employs citation analysis and co-occurrence mapping to examine the growth and evolution of the field. The results reveal a substantial increase in research activity from 2019 to 2023, with a marked rise in the number of publications and citations related to AI-driven solutions for diabetic wound management. Asian countries, particularly India and China, are identified as leading contributors in this domain, showcasing their significant role in advancing AI applications in healthcare. Through the use of VOSviewer software, the study identifies three primary research themes: AI for Automated Detection of Diabetic Foot Ulcers (DFUs) & Diabetic Retinopathy (DR), AI in Diabetic Foot Ulcers (DFUs) Diagnosis & Healing, and Diabetic Foot Ulcers (DFUs) Classification in Medical Imaging. The analysis highlights the growing importance of AI in improving the accuracy and efficiency of wound care, thus offering potential improvements in patient outcomes. This study provides valuable insights into the current landscape of AI in diabetic wound care and lays the foundation for future innovations in this crucial area of healthcare.